Rural health service leaders co‐design state‐wide research addressing an emerging health issue: A case report. (17th August 2022) - Field, Michael; Buccheri, Alison; King, Olivia; Bishop, Jaclyn; Wong Shee, Anna; Imran, Didir; Jacobs, Jane; Versace, Vincent; Isaacs, Anton; Sutton, Keith; Sourlos, Nick; Murphy, Fiona; et al.
Abstract: Aims: This commentary aims to describe a case of how meaningful co‐design between rural health service leaders and a health service‐embedded research unit can identify emerging research priorities and optimise translation. Context: The challenges facing rural health services are unique, and the important role of health service leaders in the research response is increasingly recognised. Poorly‐designed research can contribute to research waste through reduced applicability of results to rural communities, and an opportunity exists to increase research co‐designed with rural health services through the involvement of research users during study planning. Approach: In early 2020, leaders at a rural Victorian health service approached the embedded health service research unit to request research be conducted on an emerging issue: rural staff well‐being in the face of the COVID‐19 pandemic. This was based on their concern regarding the lack of available COVID‐19‐specific evidence to inform organisational policy. In collaboration with the rural health service executive, a translation‐focused study of staff well‐being with nine rural Victorian health services was developed. Key co‐design activities of the project included involving research end‐users as study investigators and conducting formal stakeholder engagement regarding study design and outcomes. Conclusion: Meaningful co‐design of research with health services is a multifaceted process that can assist researchers and end‐users alike in identifying and responding to emerging health issues. In the rural setting where there is a vital need for impactful health research, we recommend that researchers should consider employing co‐design processes in order to minimise research waste and optimise the translatability of research findings.